Structure-Properties Relationship Of Water-Blown Epoxidized Natural Rubber Foam - Harnizi, Nur Haziqah Mohd (Universiti Sains Malaysia, 2017)
The relationship between structure and properties of Epoxidized Natural Rubber (ENR) foams and distilled water as the physical blowing agent were varied to determine their effects on the morphology and mechanical properties of ENR foams. ENR foam were prepared by varying the amount of distilled water as the blowing agent. This investigation reports the mechanical properties and morphological behaviour of ENR foam by varying with the amount of blowing agent, which controls the foam architecture. The experiment was conducted by prepared four different formulation of compounding rubber which is different amount of distilled water from 0 to 3.0 parts per hundred rubber (pphr). The expandable rubber samples were prepared by using a two roll mill and expanded via a microwave oven. It was found that the mechanical properties of the ENR foam changed with the relative density of foam which is increasing the relative density, will decreasing the value of compression set. The ENR foams were characterized with respect to their crosslinking density, relative density, cell size and compression set. The results showed that the structure and properties of the rubber foams can be control by the amount of blowing agent.